Hijab Symbolism as a Medium of Da'wah in the Film Keajaiban Air Mata Wanita: A Roland Barthes Semiotic Analysis - Annisa Fatika; Tengku Walisyah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
This study aims to analyze the symbolism of the hijab in constructing the meaning of female piety in the film Keajaiban Air Mata Wanita. As a visual medium, film conveys religious values through symbols that shape audience interpretation. In this context, the hijab functions as a central symbol associated with the emotional experiences of female characters. This research uses a qualitative approach with Roland Barthes’ semiotic analysis, covering denotation, connotation, and myth. Data were collected from scenes, dialogues, and visual elements in the film and analyzed to uncover the meanings of hijab symbolism within different narrative contexts. The findings reveal that the hijab is not merely a religious attribute but a symbol consistently present in various emotional situations, such as sorrow, suffering, and relational conflict. At the levels of connotation and myth, it signifies piety through women’s ability to manage emotions, endure life’s challenges, and maintain religious identity under non-ideal conditions. Furthermore, the hijab functions as an implicit medium of religious communication through visual narratives, shaping cultural and ideological understandings of female piety.